Counteraction to Criminality In the Ukrainian SSR In the Second Half of 1930S - Греченко, Володимир (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
For today there is a far of the publications sanctified to soviet history of 1930th. However basic attention in them is spared there are 1937-1939 to strengthening of the totalitarian mode and repressions. And the problems of combating crime have received little attention.Research aim. Taking into account insufficient worked out of theme, an author put an aim to itself to light up the role of militia in counteraction to some types of criminality in the second half 1930th. This range of problems is wide enough, that is why we specially did not investigate some of directions of activity of militia at this time, in particular fight against gangsterism, counteract to economic criminality and role of militia in repressions 1937-1938, as it is an object other our scientific researches.Research methodology. The fundamental methodological principle of the study for the author was historicism. We tried to study the processes, events and facts in chronological order, taking into account the then socio-political situation. The method of comparison allowed to consider the general and special in activity of militia of different regions of the republic and differences in counteraction to different types of crimes.The scientific novelty of the article is that for the first time in the historical literature it reveals the activities of the police in combating crime in the second half of the 1930s., related to improving the work of investigators, district inspectors.In the article basic directions of activity of militia are exposed in relation to counteraction to some types of crimes in Ukraine, in the second half of 1930th. In this time a "liberal" period made off relatively in history of soviet legislation.It was considered that in connection from completion of building of socialism in the USSR the main causations of crime, related to the inheritance of, are czarism on the whole removed, and the pore of the most rapid liquidation of criminality came, although at this time appeared and new types of crimes : 1. crimes related to the passport system (imitation, sale and purchase, theft of passports); 2. violation of charter of agricultural artel, violation of soviet and of a collective farm democracy; 3.sabotage of Stakhanovsky motion, pursuit ofStakhanov’ s men.New Constitution of the USSR was accepted in 1936, and in 1937 is new Constitution of Ukraine. For them wide rights for soviet citizens were proclaimed, but in reality they were not realized, becoming illustration to neglect of law and law and order.However would be an overstatement to consider that there was complete legal anarchy and raging of criminality in the state .Conclusions. In the second half 1930th a militia, without regard to mass repressions and certain vagueness of fate of many workers, continued counteraction to criminality. Certain attention was spared to the improvement of work of investigators, district inspectors, secret-service-informative work, bringing in of public to counteraction to criminality. In the total it was succeeded to attain some reduction of general level to criminality.